Bibliographic Information on Psychology on the Sites of the Russian State Library and Universities - E. V. Gubina (Библиосфера, 2022)
In modern conditions of unstable socio-economic situation caused by the threat to human health due to the pandemic of coronavirus infection, the need for psychological information is significantly increasing. The need to assist modern readers in finding and choosing meaningful, scientifically reliable and accessible psychological information among a huge number of books and online resources has determined the relevance of the topic of the article. The article discusses popular bibliographic resources on psychology, prepared by the Research Department of Bibliography in the Russian State Library (RSL) and posted on the RSL website in the “Bibliographic publications” section: “Psychology for everyone. Index of the best books”, “Psychology. Internet Resources”, including “Psychology on the Websites of Russian Universities”. A scientific and methodological analysis of these resources is given: the criteria for their selection are shown, a variety of forms of presentation of materials is noted, accessibility for a wide range of readers is emphasized. The potential of popular bibliographic resources on psychology in the formation of a holistic view of psychological science among users and providing easy access to high-quality information on psychological issues is considered.